Evaluasi penegakan hak asasi manusia di Indonesia: Antara regulasi dan realitas - Saskia, Dwi Dita (Maliki Interdisciplinary Journal, 2026)
Human Rights are fundamental rights inherent in every human being and must be respected, protected, and fulfilled by the state. In Indonesia, regulations regarding human rights are stated in Article 28A–28J of the 1945 Constitution and Law Number 39 of 1999 concerning Human Rights. Although various regulations have been made, human rights violations still frequently occur, such as violence, discrimination, restrictions on freedom of expression, and legal injustice. This study aims to evaluate the enforcement of human rights in Indonesia by comparing applicable regulations and the reality in society. The study uses a literature study method through analysis of various sources and regulations related to human rights. The results of the study indicate that the enforcement of human rights in Indonesia still faces various obstacles, such as low public understanding, weak law enforcement, feudal culture, corrupt practices, and the less than optimal resolution of human rights violation cases. Therefore, cooperation is needed between the government, officials, law enforcement, and the community so that the enforcement of human rights in Indonesia can run fairly and effectively.